2009
DOI: 10.1002/crat.200900349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impurity ions on solubility and metastable zone width of phosphoric acid

Abstract: Key words solubility, metastable zone width, impurity ions, phosphoric acid. PACS 61.72. 64.60.My, 64.70.dg, 64.75.Bc Effects of two typical impurity ions as Fe 2+ and SO 4 2-in phosphoric acid on solubility and metastable zone width (MZW) had been studied. It was shown that polythermal method was suitable for solubility measurement in this study. The solubility experimental data was correlated with a polynomial equation. Being compared with Fe 2+, SO 4 2-had a greater impact on the phosphoric acid solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 9 publications
(10 reference statements)
2
19
0
Order By: Relevance
“…Kinetics of crystal growth Some researchers have studied thermodynamics and kinetics of phosphoric acid hemihydrate crystallization [8,11,12,15]. The stirring intensity of crystallization process has great influence on not only growth rate but also mechanism of crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetics of crystal growth Some researchers have studied thermodynamics and kinetics of phosphoric acid hemihydrate crystallization [8,11,12,15]. The stirring intensity of crystallization process has great influence on not only growth rate but also mechanism of crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the solubility of phosphoric acid increases with an increase in temperature and decreases with an increase in the concentration c i of the impurities. The authors analyzed the data using Ný vlt's equation and obtained the value of nucleation order m [11]. It was found that m increases systematically from 3.5 to 4.68 and 4.85, respectively, with an increase in the concentration of Fe 2 + and SO 2À 4 ions to 250 ppm.…”
Section: Solubility and Supersolubility Curvesmentioning
confidence: 98%
“…Recently, Ma et al [11] reported the results of an investigation of the effect of Fe 2 + and SO 2À 4 ions on the solubility and metastable zone width of phosphoric acid in the temperature range from 0 to 29.35 1C. The metastable zone width was measured by the laser intensity technique in the presence of 0.1 wt% crystal seeds.…”
Section: Solubility and Supersolubility Curvesmentioning
confidence: 99%
See 2 more Smart Citations